A state-wide economic assessment of coastal and marine ecosystem services to inform sustainable development policies in the Northern Territory, Australia. (September 2019) - Sangha, Kamaljit K.; Stoeckl, Natalie; Crossman, Neville; Costanza, Robert
Abstract: This paper offers a state-wide assessment of coastal and marine ecosystems services (ES), including Indigenous perspectives, in the Northern Territory (NT) of Australia, to inform policy developments in the region. An economic impact of AUD 1.3 billion/yr and additional economic contribution to the NT economy of AUD 1.4 billion/yr was estimated for the selected key services, in addition to affording >6, 000 jobs. The selected ES include: provisioning—commercial fisheries, and pearl and crocodile cultivation; regulating and maintenance—blue carbon, storm protection and erosion control, and genepool protection; cultural—recreational fishing, tourism, amenity and other non-fishing recreational, and Indigenous cultural values, which were evaluated applying a mix of market and non-market valuation tools. A simple framework of measuring each ES both for its 'Economic Impact'—direct and indirect market value (i.e. reflection in GDP), and 'Economic Value'—market and non-market values for their contributions to the broader NT economy (i.e. human well-being), was applied. Due to methodological limitations, Indigenous cultural values were partially measured using a substitute value for 25% of government Indigenous expenditure on four welfare sectors that relate to benefits people obtain from their coastal and marine resources. It advocates for payments for ES (PES) mechanisms to support equitable enterprises involving Indigenous communities. Overall, this economic assessment of the NT coastal and marine resources presents integrated information to initiate a dialogue on alternative and sustainable development options in the region, and can help in addressing similar development issues occurring in many parts across the globe.